TRANSFORMATION OF DIGITAL CONSUMER BEHAVIOR: THE IMPACT OF REVIEWS, RATINGS, AND VIRAL MARKETING ON PURCHASES OF SKINCARE PRODUCTS ON SHOPEE - Santoso, Adi (ITB AAS Indonesia Surakarta, 2025)
Study This aims to analyze influence review online customer review, rating customers, and viral marketing strategies towards decision purchase consumers on NPURE products on the Shopee platform. This background study rooted in the phenomenon increasing the use of e-commerce in Indonesia and shift behavior consumer in making purchase decisions influenced by digital opinions and campaigns marketing based on social media . This study use approach quantitative descriptive with method survey through questionnaire distributed to 100 respondents who were user active on Shopee and ever do purchase NPURE products . The sampling technique used is accidental sampling. Data analysis is done with Structural Equation Modeling (SEM) approach using the Partial Least Square (PLS) model through device soft SmartPLS 4. The research results show that customer rating and viral marketing variables have influence positive and significant to decision purchase . While that , the online customer review variable does not show significant influence . These findings contribute theoretically to development of behavioral models consumers in the digital era and offer implications practical for local skincare brand marketing strategies in the marketplace.